Cervical cancer screening in an indigenous population in the Brazilian Amazon: the case of DSEI Amapá and Norte do Pará and the Wajãpi Indigenous Land - Rosalen, Juliana; Gavassi, Mariana Maciel Queiroz; Fardin, Franciane Pereira; Ferron, Mariana Maleronka (O Mundo da Saúde, 2024)
Cervical cancer is a common and lethal neoplasm for women in Brazil, with an estimated 17 thousand new cases between 2023 and 2025. The North region has the highest incidence and mortality rates, reflecting inequalities in access to health services . Early detection and vaccination are essential for prevention, but coverage is insufficient when it comes to indigenous peoples. This is a descriptive study that seeks to analyze the proportion of cytopathological exams in indigenous women aged 25 to 64 years, considering two three-year periods, in accordance with the recommendations of the World Health Organization (WHO), based on data from the Information System of Cancer. The data were obtained from population data from the Special Indigenous Health District of Amapá and Norte do Pará. In the first three years (2018-2020), the proportion of exams was 3.37% in DSEI AMP and 0% in Pedra Branca do Amapari, a reference municipality for the Wajãpi people. In the second three-year period (2021-2023), these proportions increased to 21.95% and 52.38%, respectively. The significant improvement in indicators for testing among the Wajãpi is attributed to the Cervical Cancer Tracking Project, carried out by the Institute of Indigenous Research and Training (Iepé) in cooperation with the DSEI AMP. Although the collaboration between the Wajãpi, Iepé and DSEI AMP communities has produced an improvement in rates, challenges remain, especially in relation to the coverage and quality of health care provided to indigenous peoples.